2009
DOI: 10.1007/s11655-009-0458-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of Gubitong Recipe (骨痹通方) in treating osteoarthritis of knee joint

Abstract: GBT is an effective and safe recipe for the treatment of osteoarthritis of knee joint, which could alleviate the joint pain, stiffness, and dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“… 26 In fact, researchers have recently discovered that Chinese herbal medicine, a kind of complementary and alternative therapy, may alleviate the symptoms of KOA. 21 27–29 …”
Section: Introductionmentioning
confidence: 99%
“… 26 In fact, researchers have recently discovered that Chinese herbal medicine, a kind of complementary and alternative therapy, may alleviate the symptoms of KOA. 21 27–29 …”
Section: Introductionmentioning
confidence: 99%
“…Gubitong Recipe (GBT) is a prescription formulated based on the TCM theory of tonifying the kidney yang and strengthening the bone. Our previous randomized clinical trials (RCT) have shown that GBT can more effectively decrease the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score and clinical symptoms of the visual analogue scale (VAS) of OA patients in comparison with glucosamine hydrochloride, reduce the amount of diclofenac sodium use, and has no obvious side effects [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Three trials reported mild gastrointestinal symptoms in the TCM groups (Kang et al , 2011; Tao et al , 2012; Zhu et al , 2013). Eight trials reported gastrointestinal symptoms, renal dysfunction, hematochezia, liver dysfunction, paresthesia of the mouth and tongue, skin allergy, and headache in the control groups (Deng, 2008; Deng and Ding, 2009; Han, 2014; Kang et al , 2011; Liu et al , 2012; Tao et al , 2012; Zhu et al , 2013). No serious adverse events occurred.…”
Section: Resultsmentioning
confidence: 99%